Systemic immune‐checkpoint blockade with anti‐PD1 antibodies does not alter cerebral amyloid‐β burden in several amyloid transgenic mouse models. Issue 3 (14th November 2017) - Latta‐Mahieu, Martine; Elmer, Bradford; Bretteville, Alexis; Wang, Yaming; Lopez‐Grancha, Mati; Goniot, Philippe; Moindrot, Nicolas; Ferrari, Paul; Blanc, Véronique; Schussler, Nathalie; Brault, Emmanuel; Roudières, Valérie; et al.
Abstract: Chronic inflammation represents a central component in the pathogenesis of Alzheimer's disease (AD). Recent work suggests that breaking immune tolerance by Programmed cell Death‐1 (PD1) checkpoint inhibition produces an IFN‐γ‐dependent systemic immune response, with infiltration of the brain by peripheral myeloid cells and neuropathological as well as functional improvements even in mice with advanced amyloid pathology (Baruch et al., (2016 ): Nature Medicine, 22:135–137). Immune checkpoint inhibition was therefore suggested as potential treatment for neurodegenerative disorders when activation of the immune system is appropriate. Because a xenogeneic rat antibody (mAb) was used in the study, whether the effect was specific to PD1 target engagement was uncertain. In the present study we examined whether PD1 immunotherapy can lower amyloid‐β pathology in a range of different amyloid transgenic models performed at three pharmaceutical companies with the exact same anti‐PD1 isotype and two mouse chimeric variants. Although PD1 immunotherapy stimulated systemic activation of the peripheral immune system, monocyte‐derived macrophage infiltration into the brain was not detected, and progression of brain amyloid pathology was not altered. Similar negative results of the effect of PD1 immunotherapy on amyloid brain pathology were obtained in two additional models in two separate institutions. These results show that inhibition of PD1 checkpoint signaling by itself is not sufficient to reduce amyloid pathology and that additional factors might have contributed to previously published results (Baruch et al., (2016 ): Nature Medicine, 22:135–137). Until such factors are elucidated, animal model data do not support further evaluation of PD1 checkpoint inhibition as a therapeutic modality for Alzheimer's disease. Main Points: Treatment with anti‐PD1 had previously been shown to reduce brain amyloid load in transgenic mice. We failed to reproduce this effect in three different animal models. At this stage, limited evidence supports use of anti‐PD1 therapy in Alzheimer's disease.